Pulmonary Alveolar Proteinosis in Setting of Inhaled Toxin Exposure and Chronic Substance Abuse - Meirui Li; Salem Alowami; Miranda Schell; Clive Davis; Asghar Naqvi (Case Reports in Pulmonology)
Pulmonary alveolar proteinosis (PAP) is a rare lung disorder in which defects in alveolar macrophage maturation or function lead to the accumulation of proteinaceous surfactant in alveolar space, resulting in impaired gas exchange and hypoxemia. PAP is categorized into three types: hereditary, autoimmune, and secondary. We report a case of secondary PAP in a 47-year-old man, whose risk factors include occupational exposure to inhaled toxins, especially aluminum dust, the use of anabolic steroids, and alcohol abuse, which in mice leads to alveolar macrophage dysfunction through a zinc-dependent mechanism that inhibits granulocyte macrophage-colony stimulating factor (GM-CSF) receptor signalling. Although the rarity and vague clinical presentation of PAP can pose diagnostic challenges, clinician awareness of PAP risk factors may facilitate the diagnostic process and lead to more prompt treatment.